Exploring the Relative Importance of Factors That Influence Student-Athletes’ School-Choice Decisions: A Case Study of One Canadian University - Chard, Chris R.; Potwarka, Luke R. (Journal of Intercollegiate Sport, 2017)
Understanding salient factors influencing student-athletes’ decisions to attend particular university institutions is of crucial importance to scholars and athletic administrators. Consequently, our research was concerned with two separate but interrelated substantive and methodological objectives: i) to gain insights into the relative importance of 12 school choice decision-making factors influencing Canadian student-athletes; and ii) to explore the efficacy of a multicriteria decision-making (MCDM) method for analyzing data in the context of the current investigation. Specifically, we employed the Analytic Hierarchy Process (AHP) to better understand the relative importance of school choice decision factors. The results of the AHP analysis on Canadian student-athletes’ school choice decisionmaking showed that having the desired academic program was the most important influence. This item was almost twice as important as the reputation of the school, and over twice as important as scholarship value, athletic facilities, chance to win, and reputation of the head coach. Of the 12 factors considered, these six had the greatest influence on student-athletes’ decision-making. Implications of our findings for research and recruitment efforts are discussed.